Fear appeal intensity in road safety advertisements and strength of negative emotions - Veljanova Radica; Ciunova shuleska, Anita (My University, 2019)
Fear appeals are a kind of "external inducers" that are used to increase the desire of the individuals to do something useful and good, not only for themselves but for the environment, for the society and for the family as well. Fear appeals are related to various forms of emotional components that are basically negative, such as fear, sadness, guilt, depression, etc., which serve to motivate the individual, to make a change in the same direction with the guidelines promoted by the message with fear appeal. The aim of this paper is to investigate the relationship of advertisements with different fear appeal intensity with certain types of negative emotions. Actually, we tested if there are significant differences in the impact of advertisements with low and high fear appeal intensity on six different types of negative emotions. This research study relies on the linear model and Extended parallel processing model assuming that advertising message effectiveness measured through the strength of negative emotions is different depending on the message fear appeal intensity. A survey with 100 respondents (who possess driving licence) was carried out, using questionnaires as a method of data collection. To measure the influence of advertising messages with fear appeal on negative emotions a survey questionnaire was developed.Non-probability sampling procedure (convenient sampling) was used to design the research sample. Kruskal-Wallis test was used to reveal the differences in the strength of negative emotions evoked by the advertising messages with different fear appeal intensity. The results indicated that there are significant differences between advertisements with high and advertisements with low fear appeal intensity on five negative emotions. Actually, there are siginificatnt differenes in the strength of guilt, anger, fear, anxiety and sorrow between advertising messages with high and low fear appeal intensity. Messages with high fear appeal intensity evoke stronger emotions of guilt, anger, fear, anxiety and sadness compared to messages with low fear appeal intensity. Despite several limitations, this study offers valuable findings and poses some directions for further research. Namely, this study offers valuable insights into the relationship between advertising messages with different fear appeal intensity and negative emotions providing marketing managers and particularly marketing communications managers some useful guidelines for effective decision making regarding the communications strategy. The limitations of this research can be overcome in the future by concentrating on the effect of different fear appeal intensity on recall or attitude change. Also examining the effect of fear type and fear intensity might be an interesting research topic as well. Furthermore, personality traits could be more carefully explored and linked with the effectiveness of fear appeal advertisements.
Keywords: advertising messages, fear appeal intensity, negative emotions